Toward a theory of business. (2015) - Donaldson, Thomas; Walsh, James P.
Abstract: What is the purpose of business? While most agree that business minimally involves the creation of value, a blurred double image of value haunts our discussion of purpose. The image of what counts as value for a single firm is laid atop an image of what counts as value for business in general. These two images cannot match. Indeed, the resulting conceptual blurriness is a classic example of a composition fallacy. We should never mistake the properties of a part for the properties of the whole. A theory of the firm is ill equipped to handle the many expectations we hold for business practice. As such, we seek to establish the beginnings of a theory of business, one that is both empirical and normative. Offering four central propositions about the purpose, accountability, control and success of business, we close with a consideration of several important theoretical issues and practical opportunities that await us in the years ahead.